Magnetic metal organic framework hydrogel composite material as well as preparation method and application thereof

By combining magnetic metal organic frame particles with hydrogels, magnetic MOFs hydrogel composites are formed, which solves the sensitivity and long time problems when detecting malachite green in aquatic products, and achieves efficient and rapid adsorption and detection effects.

CN119386829APending Publication Date: 2025-02-07BEIJING TECH & BUSINESS UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411321006.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has problems such as insensitive detection and long pretreatment detection time when detecting malachite green in aquatic products.

Method used

Magnetic metal organic frame hydrogel composite material is used to combine magnetic metal organic frame particles with hydrogel to form magnetic MOFs hydrogel composite material, increasing its adsorption position on malachite green, thereby improving adsorption capacity.

Benefits of technology

This material significantly improves the adsorption ability and detection sensitivity to malachite green, shortens the detection time, and maintains a good adsorption effect during reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386829A_ABST
    Figure CN119386829A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic metal organic framework hydrogel composite material as well as a preparation method and application thereof, and belongs to the technical field of detection. The magnetic metal organic framework hydrogel composite material is obtained by compounding magnetic metal organic framework particles and hydrogel; the magnetic metal organic framework particles are particles formed by coating Fe3O4 with MOF-545 (metal organic framework); the hydrogel is a cross-linked polymerization network formed by polymerization of polyacrylamide and sodium alginate; the magnetic metal organic framework is dispersed in the cross-linked polymerization network. The composite material has good adsorption capacity on malachite green dye, has good stability, portability and repeatability, and still has a relatively good adsorption effect on the malachite green dye under the condition that the composite material is repeatedly used for 6 times. The composite material can be used as a very promising material for separating and determining malachite green pollutants from aquatic products, and the rapid adsorption and enrichment effect of the composite material on malachite green greatly shortens the detection time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a magnetic metal organic framework hydrogel composite material and a preparation method and application thereof, belonging to the field of detection technology. Background Art

[0002] Malachite green is an organic synthetic dye, commonly used in the dyeing of clothing fabrics. It is also a disinfectant. In food, it was often used to disinfect aquatic products to prevent fish from being infected with fungi. Long-term use of this malachite green to disinfect aquatic products will cause great harm to the human body and cause serious carcinogenesis. my country has banned the addition of malachite green in aquaculture, but some businesses still use this method to cultivate aquatic products in order to obtain greater profits, which has caused great harm to the human body and the environment. The traditional methods for detecting malachite green in aquatic products include extraction, adsorption, physical and chemical testing, and immunological testing. Among these tests, adsorption is the most time-saving and labor-saving method. The materials commonly used for the adsorption of malachite green are activated carbon, MOFs, COFs porous materials, etc. At present, these methods still have shortcomings such as insensitive detection and long pre-treatment detection time. Therefore, a method for rapid detection of malachite green is very needed. Summary of the invention

[0003] In order to solve the problems of insensitive detection and long pre-treatment detection time in the existing technology for the determination and separation of malachite green in aquatic products, the present application provides a magnetic metal organic framework hydrogel composite material and a preparation method and application thereof, in which a metal organic framework material is combined with a hydrogel to form a magnetic MOFs hydrogel composite material, which increases many adsorption sites for malachite green dye, thereby increasing the adsorption capacity for malachite green dye.

[0004] This application adopts the following technical solutions:

[0005] According to one aspect of the present application, a magnetic metal-organic framework hydrogel composite material is provided, wherein the magnetic metal-organic framework hydrogel composite material is obtained by compounding magnetic metal-organic framework particles and hydrogel;

[0006] The magnetic metal organic framework particles are particles of MOF-545 coated with Fe3O4;

[0007] The hydrogel is a cross-linked polymer network formed by polymerization of polyacrylamide and sodium alginate;

[0008] The magnetic metal organic framework is dispersed in the cross-linked polymeric network.

[0009] Optionally, the surface of the magnetic metal-organic framework hydrogel composite material has a small pore structure formed by grooves and unevenness.

[0010] Optionally, the particle size of the magnetic metal-organic framework hydrogel composite material is 1 to 5 mm.

[0011] The texture of hydrogel is soft and can maintain a certain shape. Metal organic framework materials are combined with hydrogel to form a new type of material, hydrogel magnetic nanocomposite. Using hydrogel as a carrier can more effectively and easily recycle magnetic nanocomposites, and improve the detection sensitivity of malachite green through directional modification. Wrapping hydrogel on the surface of magnetic nanomaterials can increase the stability of magnetic nanomaterials and improve their portability. The hydrogel magnetic nanocomposite adsorbs malachite green more quickly and accurately.

[0012] According to another aspect of the present application, a method for preparing the magnetic metal organic framework hydrogel composite material is provided, characterized in that it comprises the following steps:

[0013] S1, obtaining magnetic metal organic framework particles;

[0014] S2, mixing solution A containing magnetic metal organic framework particles, polyacrylamide, an initiator, and a cross-linking agent with solution B containing sodium alginate, and then adding tetramethylethylenediamine to obtain a mixed solution;

[0015] S3, dropping the mixed solution into a calcium chloride solution, stirring, and filtering to obtain the magnetic metal organic framework hydrogel composite material.

[0016] Optionally, in step S2, the initiator is selected from sodium persulfate.

[0017] Optionally, the cross-linking agent is selected from N,N-methylenebisacrylamide.

[0018] Optionally, in step S2, the solid-to-liquid ratio of the magnetic metal organic framework particles to polyacrylamide in solution A is 1 mg: 0.07-0.11 mL.

[0019] Optionally, the solid-liquid ratio of the magnetic metal organic framework particles to the initiator is 1 mg: 2 to 2.5 μL.

[0020] Optionally, the solid-liquid ratio of the magnetic metal organic framework particles to the cross-linking agent is 1 mg: 8 to 12 μL.

[0021] Optionally, the percentage concentration of sodium alginate in solution B is 3.8-4.2 wt %.

[0022] Optionally, the solid-liquid ratio of the magnetic metal organic framework particles to solution B is 1 mg: 0.05-0.1 mL.

[0023] Optionally, the solid-liquid ratio of the magnetic metal organic framework particles to tetramethylethylenediamine is 1 mg: 0.5-1 μL.

[0024] Optionally, the concentration of the calcium chloride solution is 0.1-0.3 mol / L.

[0025] Optionally, in step S3, the stirring conditions include: stirring time is 0.9 to 1.1 h.

[0026] Optionally, in step S1, the preparation process of magnetic metal organic framework particles includes:

[0027] S1-1: Fe3O4 magnetic nanoparticles are mixed with polyvinyl pyrrolidone to obtain Fe3O4@PVP magnetic particles;

[0028] S1-2: The Fe3O4@PVP magnetic particles and MOF-545 are mixed and subjected to a solvothermal reaction I to form a Fe3O4@MOF-545 composite, thereby obtaining the magnetic metal organic framework particles;

[0029] Wherein, the mass ratio of the Fe3O4 magnetic nanoparticles to polyvinyl pyrrolidone is 1:4-6;

[0030] The temperature of the solvent thermal reaction I is 85-95° C., the reaction time is 5-7 hours, and the solvent I is N,N-dimethylformamide.

[0031] Optionally, in step S1, in step S1-1, the specific preparation process of the Fe3O4@PVP magnetic particles includes: mixing ferric chloride, ferrous chloride and a solvent to obtain a mixture, stirring the mixture and ammonia water at a temperature of 55 to 65°C for 10 to 30 minutes, and obtaining Fe3O4 magnetic nanoparticles after magnetic separation; the Fe3O4 magnetic nanoparticles are mixed with polyvinyl pyrrolidone, vortexed at room temperature for 18 to 22 hours, and obtaining Fe3O4@PVP magnetic particles after magnetic separation;

[0032] Wherein, the mixing ratio of the ferric chloride, the ferrous chloride and the ammonia water is 50-55g:30-35g:190-210mL;

[0033] Optionally, in step S1-2, the specific preparation process of the Fe3O4@MOF-545 composite includes:

[0034] The Fe3O4@PVP magnetic particles, tetrakis(4-carboxyphenyl)porphyrin, ZrOCl2·8H2O and benzoic acid are mixed, subjected to solvothermal reaction I, and magnetic separation is performed to obtain a Fe3O4@MOF-545 composite;

[0035] The mass ratio of the Fe3O4@PVP magnetic particles to the tetrakis(4-carboxyphenyl)porphyrin is 1:1;

[0036] The mass ratio of the tetrakis(4-carboxyphenyl)porphyrin, the ZrOCl2·8H2O and the benzoic acid is (40-60):(140-160):(2700-2900).

[0037] According to another aspect of the present application, there is provided a use of the above-mentioned magnetic metal organic framework hydrogel composite material or the magnetic metal organic framework hydrogel composite material obtained according to the above-mentioned preparation method as an adsorption material in the separation and determination of malachite green from aquatic products.

[0038] The beneficial effects of this application include:

[0039] The magnetic metal organic framework hydrogel composite material provided in the present application is a composite material formed by combining a metal organic framework material Fe3O4@MOF-545 with a hydrogel PAAM-SA. It has good adsorption capacity for malachite green dye, good stability and portability. The combination of hydrogel and Fe3O4@MOF-545 improves the antioxidant property of the material, making it more convenient to store than other materials. When the composite material is dried and stored for 25 days, the composite material microspheres can also adsorb malachite green dye very well and show good repeatability. It can be reused 6 times and still has a good adsorption effect on malachite green dye. This material can be used as a very promising composite material for separating and determining malachite green pollutants from aquatic products. It has better ability to adsorb and elute malachite green. Its rapid adsorption and enrichment effect on malachite green greatly speeds up the detection time. When the sodium alginate concentration is 4.2%, the mass is 2.5ml, the Fe3O4@MOF-545 mass is 30mg, and the solution pH is 6, the adsorption effect on malachite green is the best, and the adsorption rate can reach 96.5%. Acetonitrile is used as the eluent, the elution volume is 5mL, and the elution rate can reach 99.1% in 6 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the preparation, adsorption and desorption process and structural formula of PAAM-SA / Fe3O4@MOF-545 microspheres in this application.

[0041] Figure 2These are the SEM images of the PAAM-SA / Fe3O4@MOF-545 microspheres of the present application, wherein (A) to (C) are SEM images of PAAM-SA / Fe3O4@MOF-545 at different sizes of 1 mm, 20 μm, and 70 μm before adsorption, (D) to (F) are element mapping diagrams (O, Fe, Zr) of PAAM-SA / Fe3O4@MOF-545 before adsorption, (G) to (I) are SEM images of PAAM-SA / Fe3O4@MOF-545 at different sizes of 1 mm, 20 μm, and 70 μm after adsorption, and (J) to (L) are element mapping diagrams (O, Fe, Cl) of PAAM-SA / Fe3O4@MOF-545 after adsorption.

[0042] Figure 3 This is the infrared spectrum of this application, and from bottom to top in the spectrum are the infrared spectra of hydrogel microspheres, magnetic hydrogel microspheres and magnetic MOFs hydrogel microspheres.

[0043] Figure 4 This is the effect of different conditions on the decolorization rate of this application, where (A) is the effect of hydrogel concentration on the decolorization rate, (B) is the effect of hydrogel quality on the decolorization rate, (C) is the effect of magnetic MOFs quality on the decolorization rate, and (D) is the effect of non-magnetic MOFs, magnetic MOFs, and magnetic MOFs on the decolorization rate.

[0044] Figure 5 The effects of different conditions on the adsorption performance of this application, including (A) the effect of different MG initial concentrations on the adsorption performance of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres; (B) the effect of different PAAM-SA / Fe3O4@MOF-545 hydrogel microsphere masses on the decolorization rate; (C) the effect of adsorption time on the adsorption performance of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres; (D) the effect of different MG solution pH on the adsorption performance of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres.

[0045] Figure 6 This is the adsorption kinetic model of the present application, wherein (A) is a pseudo-first-order adsorption kinetic model; (B) is a pseudo-second-order adsorption kinetic model.

[0046] Figure 7 The effects of different conditions on the elution rate of this application, where (A) is the effect of the eluent volume on the elution rate; (B) is the effect of the elution time on the elution rate; (C) is the effect of the mass of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on the elution rate; (D) is the effect of different eluent types on the elution rate.

[0047] Figure 8The effects of the storage time of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on the adsorption performance of this application are shown in Figure 2, wherein (A) is the adsorption rate of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on different materials; (B) is the effect of the recycling of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on malachite green; (C) is the effect of the storage time of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on the adsorption effect; (D) is the effect of the storage time of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on the elution effect. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0050] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0051] N,N-dimethylacetamide (DMF, 99.5%), ethanol (99.5%).

[0052] Vortex oscillator (VM-500pro); magnetic stirrer; Shimadzu UV-3600Plus ultraviolet-visible spectrophotometer; H1850 centrifuge; oil bath; pH meter; scanning electron microscope (model: Thermo Fisher Quarttor S; energy spectrum: EDAX ELECT PIUS); Fourier transform infrared absorption spectrometer (FTIR) (model: Thermo Nicolet iS5); liquid chromatography-triple quadrupole mass spectrometer (Agilent 1290 first generation).

[0053] In the test example of the present application, the malachite green solution was prepared by first dissolving 100 mg of malachite green in 100 mL of ultrapure water to obtain a malachite green solution with a concentration of 100 mg / L. The malachite green solution was then diluted with ultrapure water to concentrations of 1, 2, 3, 4, and 5 mg / L. The absorbance of the malachite green solution was then detected by an ultraviolet spectrophotometer at a wavelength of 616 nm to obtain a standard absorbance curve with a linear equation of A=0.035C-0.004, R 2 =0.999 (A is absorbance, C is the concentration of malachite green solution, R 2 is the correlation coefficient). Malachite green solutions with concentrations of 0.3, 0.4, 1, 1.5, 2.5, 10, and 20 μg / L were prepared and tested using UPLC-MS / MS to obtain a linear equation that can be used to test actual samples.

[0054] The adsorption performance and separation of malachite green in the test example of this application are as follows: 300 mg of PAAM-SA / Fe3O4@MOF-545 is used to adsorb 10 mL of malachite green solution with a concentration of 100 mg / L and a pH value of 6, and the solution is detected by ultraviolet spectrophotometry. The decolorization rate is calculated according to formula (1).

[0055]

[0056] In the formula, the absorbance of the original solution is C0, the absorbance of the solution after adsorption is C1, and X is the decolorization rate.

[0057] Fish and shrimp were used as actual samples to detect and separate the malachite green content in the body. First, 10g of the sample was soaked in pure water, and then the PAAM-SA / Fe3O4@MOF-545 microspheres were placed in the sample to be tested and waited for 30 minutes to allow the malachite green to be completely adsorbed on the microspheres to play a role in separation. The microspheres were magnetically separated and eluted with 5mL of acetonitrile. Finally, the purified malachite green solution and sample solution were analyzed by UPLC-MS / MS.

[0058] The HPLC-MS / MS parameter conditions in the test example of this application are as follows: the flow rate is 400 μL / min, and (A) 5mmol / L ammonium acetate and (B) acetonitrile containing 0.1% formic acid are used as the mobile phase. The chromatographic column uses C18 (4.6mm×100mm, particle size is 1.8μm), the column temperature is 25°C, and the injection volume is 20μL. The ion source uses the point spray ESI positive ion mode and the multiple reaction detection MRM scanning mode. The proposed method has been verified in terms of linear detection limit and quantification limit, and the standard error value is obtained by testing the sample three times.

[0059] Preparation Example 1 Preparation of Fe3O4@MOF-545

[0060] (1) Preparation of Fe3O4: Weigh 53.17 g of ferric chloride hexahydrate and 32.6 g of ferrous chloride tetrahydrate, dissolve them in a reactor containing 1.5 L of ultrapure water and 2 L of ethanol under a nitrogen atmosphere, and mix them; after blowing nitrogen for 30 min, quickly add 200 mL of ammonia water to the mixture, and mechanically stir at 60°C for 20 min; after the reaction, collect the synthesized black Fe3O4 nanoparticles by magnetic separation, wash them once with 1% sodium citrate solution, deionized water, and ethanol in turn; finally, disperse the washed Fe3O4 nanoparticles in deionized water for later use.

[0061] (2) Preparation of Fe3O4@PVP: Add five times the amount of polyvinyl pyrrolidone (PVP) powder (750 mg) to the prepared Fe3O4 solution (25 mL, 6 mg / mL), mix the two, and vortex at room temperature for 20 h. Collect the prepared Fe3O4@PVP by magnetic separation, wash it twice with water, transfer it to N,N-dimethylformamide (DMF), and wash until the supernatant is clear. Finally, dissolve the Fe3O4@PVP in DMF for later use.

[0062] (3) Preparation of Fe3O4@MOF-545: The obtained magnetic particles (50 mg) were dissolved in 10 mL of DMF solution; then, they were transferred to a round-bottom flask containing tetrakis(4-carboxyphenyl)porphyrin (TCPP) (50 mg), ZrOCl2·8H2O (150 mg) and benzoic acid (2.8 g) by magnetic separation, and DMF was added to make the final volume of the solvent 50 mL (containing 2% v / v water). After ultrasonic treatment until complete dissolution, the mixture was stirred and heated in an oil bath at 90°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature, the product was collected by magnetic separation, and washed three times with DMF to finally obtain Fe3O4@MOF-545 particles.

[0063] Example 1 Synthesis of magnetic metal organic framework hydrogel composite material

[0064] Take 30mg of the prepared Fe3O4@MOF-545, 2.75ml of polyacrylamide (PAAm) solution, 70ul of sodium persulfate APS (photoinitiator), and 300ul of N,N-methylenebisacrylamide BIS (crosslinker) and add them to syringe A. Add 2.5ml of 4.2wt% sodium alginate (SA) solution to syringe B. Mix the solutions of syringe A and syringe B with a syringe coupler, and then mix 20ul of N,N,N9,N9-tetramethylethylenediamine (TMED) with the syringe coupler to obtain a mixed solution. Then, Figure 1 As shown, the mixed solution was dropped into an anhydrous calcium chloride solution with a concentration of 0.2 mol / L using a syringe, and then filtered and dried after magnetic stirring for 1 hour to obtain microspheres of magnetic metal organic framework hydrogel composite material, named PAAM-SA / Fe3O4@MOF-545, which is marked as magnetic MOFs hydrogel in the accompanying figure.

[0065] Comparative Example 1 Synthesis of hydrogel

[0066] Take 2.75ml of PAAM solution, 70ul of APS (photoinitiator), and 300ul of BIS (cross-linking agent) and add them to syringe A, add 2.5ml of 4.2% sodium alginate solution to tube B for coupling, then add 20ul of TMED and drip it into anhydrous calcium chloride solution with a concentration of 0.2mol / L with a syringe. After magnetic stirring for 1h, filter and dry to obtain hydrogel microspheres, named PAAM-SA, and marked as sodium alginate in the accompanying drawings.

[0067] Comparative Example 2 Synthesis of magnetic hydrogel

[0068] Take 30mg Fe3O4 powder, 2.75ml PAAM solution, 70ul APS (photoinitiator), and 300ul BIS (cross-linking agent) and add them to syringe A, add 2.5ml of 4.2% sodium alginate solution to tube B for coupling, then add 20ul TMED and drip it into anhydrous calcium chloride solution with a concentration of 0.2mol / L with a syringe. After magnetic stirring for 1h, filter and dry to obtain magnetic hydrogel microspheres, named PAAM-SA / Fe3O4, marked as magnetic hydrogel in the accompanying figure.

[0069] Test Example 1 Characterization of PAAM-SA / Fe3O4@MOF-545

[0070] A malachite green solution with a concentration of 100 mg / mL and a pH of 6 was prepared, and 300 mg of PAAM-SA / Fe3O4@MOF-545 composite microspheres were used to adsorb the malachite green solution for 30 minutes. The morphology and size of the materials before and after the adsorption of PAAM-SA / Fe3O4@MOF-545 composite microspheres were analyzed by SEM to study the mechanism of adsorption of malachite green dye by magnetic MOFs hydrogel microspheres. The results are as follows: Figure 1 As shown in the SEM image, it can be clearly observed that Figure 2 A- Figure 2 C and after adsorption Figure 2 G- Figure 2 I. Changes in structure. Figure 2 A and Figure 2 G It can be seen that the PAAM-SA / Fe3O4@MOF-545 composite microspheres before adsorption are a complete structure with obvious grooves and unevenness, which together constitute a small pore structure, thereby increasing the specific surface area of ​​the microspheres and adding many adsorption sites for malachite green dye, thereby increasing the adsorption capacity of malachite green dye. After adsorption, the surface grooves become fewer and shallower. Figure 2 B. Figure 2 C. Figure 2 H. Figure 2It can be clearly seen that the surface grooves have changed significantly before and after adsorption. It can be seen that the surface has become much smoother after adsorption, indicating that the malachite green dye has been successfully adsorbed on the surface of the microspheres. Figure 2 D- Figure 2 The mapping diagram of F confirms the distribution of O, Fe, and Zr on the microspheres before adsorption. Figure 2 J- Figure 2 L confirmed the distribution of O, Fe, and Cl on the surface of the microspheres after adsorption.

[0071] The infrared spectra of the hydrogel microspheres prepared in Comparative Example 1, the magnetic hydrogel microspheres prepared in Comparative Example 2, and the magnetic MOFs hydrogel microspheres prepared in Example 1 are shown in FIG. Figure 3 As shown in the figure, the infrared spectrum of pure hydrogel microspheres at 3406 cm -1 and 3243cm -1 There are two peaks at 3363 cm in the infrared spectra of magnetic hydrogel microspheres and magnetic MOFs hydrogel microspheres. -1 、3392cm -1 It is caused by the stretching vibration of the hydroxyl groups of water molecules in the microspheres and the hydroxyl groups in sodium alginate. The peak width of magnetic hydrogel microspheres and magnetic MOFs hydrogel microspheres compared with pure hydrogel microspheres is due to the overlap of hydroxyl and -NH stretching. The peak width of pure hydrogel microspheres is 1646cm -1 and 1622cm -1 The two peaks appearing at 1436 cm-1 are characteristic absorption peaks of carboxylic acid polymers, and the stretching vibration peak of amino groups on magnetic MOFs is at 1436 cm-1. -1 The vibration peak of Fe-O appears at 1447cm -1 Pure hydrogel microspheres and magnetic MOFs hydrogel microspheres at 1011cm -1 With 1012cm -1 The peak appearing at is the ether bond.

[0072] Test Example 2 Optimization test of adsorption conditions

[0073] Sodium alginate is one of the important raw materials for making PAAM-SA / Fe3O4@MOF-545 microspheres. It can improve the stability and portability of microspheres. Different sodium alginate contents have different effects on the adsorption of malachite green dye by microspheres. By changing the concentration and quality of sodium alginate during the preparation process, the results showed different degrees of effect on the adsorption of malachite green dye by microspheres. Figure 4 A. Figure 4 As shown in B, the preparation method is consistent with Example 1, except that the percentage concentration of sodium alginate is set between 3% and 4.2%, and the mass of sodium alginate is set between 1 and 4.2 mL. When the concentration and mass of sodium alginate reach 4.2% and 2.5 mL, the microspheres achieve the maximum decolorization rate of malachite green dye.

[0074] The adsorption capacity is also related to the weight of magnetic MOFs contained in the microspheres. Figure 4 As shown in C, the preparation method is consistent with that in Example 1, except that when the mass of the magnetic MOFs is between 30 and 45 mg, it can be seen that as the mass of the magnetic MOFs increases, the decolorization rate decreases accordingly. Therefore, when the mass of the magnetic MOFs is 30 mg, the decolorization rate reaches 99.3%, and the PAAM-SA / Fe3O4@MOF-545 microspheres achieve the optimal adsorption rate of malachite green dye.

[0075] The adsorption of malachite green dye by PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres containing magnetic MOFs was compared with that by hydrogel microspheres without adding magnetic MOFs and magnetic hydrogel microspheres only adding Fe3O4 under the same conditions. Figure 4 As shown in Figure D, the decolorization rate of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres containing magnetic MOFs reached 96.5%, while the decolorization rates of hydrogel microspheres without magnetic MOFs and magnetic hydrogel microspheres with only Fe3O4 on malachite green dye were only 59.9% and 71%, respectively. The adsorption effect of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on malachite green dye was significantly higher than that of hydrogel microspheres and magnetic hydrogel microspheres. This result shows that the combination of magnetic MOFs and hydrogels is very successful, and it also solves the problem of traditional adsorption of malachite green dye and the problem of low adsorption rate of hydrogels.

[0076] In order to determine the maximum adsorption effect of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on malachite green dye, malachite green solutions with different concentration gradients were prepared ( Figure 5 A) The concentrations were set to 100 mg / L, 200 mg / L, 300 mg / L, and 400 mg / L, and the pH value of the malachite green solution was adjusted to 6. 300 mg of the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres prepared in Example 1 were placed in 10 mL of the prepared malachite green solution, and the solution was tested after vortexing for 30 min. It was found that when the concentration of the malachite green solution was 100 mg / L, the material had the greatest adsorption effect on it. The reason why the adsorption effect was not good when the concentration was too high was that malachite green had occupied the adsorption sites on the surface of the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres, and other adsorption sites could not be found or the time to find the adsorption sites was long.

[0077] In order to find the appropriate mass of material for adsorption, the malachite green solution concentration was 100 mg / mL and the pH was 6. The weight of the material was added at 50 mg, 100 mg, 200 mg, 300 mg, 400 mg, and 500 mg respectively. The results in the figure show that when the weight of the material is above 200 mg, the decolorization rate remains almost unchanged at about 95% ( Figure 5 B). This is because when the weight of the material is 200 mg, the adsorption sites of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres for malachite green dye have almost reached a state of equilibrium. On this basis, further adding this microsphere material will not have a more obvious adsorption effect on malachite green dye. By changing the physical conditions of the adsorption environment and using the vortex vibration method to increase the interaction between the microspheres and the adsorbed solvent, the adsorption time can be accelerated to within 30 minutes ( Figure 5 C). At 30 minutes, the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres and malachite green solution reached a saturated state, and the decolorization rate was 91.5%. The pH value of the malachite green solution has a crucial influence on the adsorption efficiency of the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres, which affects both the ionic state of the malachite green solution and the positive and negative charges of the functional groups on the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres. In order to study the effect of pH on the adsorption efficiency, the pH of the malachite green solution was adjusted to 2 to 9, and then 200 mg of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres were added to the solution. The results are shown in the figure. Figure 5 As shown in D, when the pH value is 2 to 4, the H + More will form a competitive relationship with malachite green, and will combine with the malachite green dye and the negative charge of the functional group on the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres, resulting in a decrease in the binding rate of the malachite green dye, and thus a decrease in the adsorption rate. The adsorption rate is the best at pH 6. At pH 7-9, the carboxyl groups on the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres are ionized, resulting in a decrease in the adsorption rate of malachite green. However, because there is an electrostatic interaction between malachite green and the adsorbent, the adsorption rate in an alkaline environment is higher than that in a strongly acidic environment.

[0078] Test case 3: separation mechanism

[0079] In order to further study the adsorption kinetics of malachite green dye on PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres, the pseudo-first-order kinetic model and pseudo-second-order kinetic model were used. Figure 6As shown, the relevant parameters are shown in Tables 1 and 2. Pseudo-first-order kinetics, pseudo-second-order kinetics and intra-particle diffusion kinetics model calculation formulas (1), (2), and (3).

[0080]

[0081] Qt=K3t 0.5 +C (3)

[0082] In this formula, Qe is the adsorption amount at equilibrium time, mg / g; Qt is the adsorption amount at time t, mg / g; K1 is the pseudo-first-order kinetic rate constant, K2 is the pseudo-second-order kinetic rate constant, K3 is the intra-particle diffusion kinetic model, t is time, and C is the boundary layer thickness. It can be seen from Table 3 that the correlation coefficient R of the pseudo-first-order kinetic model 2 The value is 0.007, and the pseudo-second-order kinetic model R 2 The value of 0.999 indicates that the pseudo-second-order kinetic model has a better fitting effect, and the rate constants of the pseudo-first-order kinetic model and the pseudo-second-order kinetic model are both greater than 0.9, indicating that both the pseudo-first-order kinetic model and the pseudo-second-order kinetic model can be used to describe the adsorption kinetics of malachite green dye by PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres. Because the rate constant of the pseudo-first-order kinetic model is greater than the rate constant of the pseudo-second-order kinetic model, and the Qe value is closer to the true value, the adsorption process of malachite green dye by PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres is mainly dominated by physical adsorption.

[0083] In order to further understand the control steps of the adsorption rate at each stage, the intra-particle diffusion kinetic model was used for research. C is not 0, and the fitting curve does not pass through the zero point, indicating that the internal diffusion is not the only rate-limiting step, and it includes both intra-particle diffusion and surface diffusion. K1>K2>K3 indicates that the adsorption sites on the surface of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres are occupied by the adsorbed substances, the adsorption rate slows down, and finally reaches equilibrium.

[0084] Table 1 Power parameters

[0085]

[0086] Table 2 Intraparticle diffusion model parameters

[0087]

[0088] Test Example 4 Optimization test of elution conditions

[0089] Malachite green dye was eluted with different organic solvents, and acetonitrile was the best elution solvent. Figure 7 D) Figure 7 A and Figure 7 As shown in AC, the elution rate is different for different eluent volumes and PAAM-SA / Fe3O4@MOF-545 hydrogel microsphere masses. The best elution rate is achieved when the eluent is 5 mL and the PAAM-SA / Fe3O4@MOF-545 hydrogel microsphere mass is 190 mg. Figure 7 As shown in B, the elution rate reached 98% when the elution time was 3 minutes, and the adsorption equilibrium state was achieved at the 7th minute.

[0090] Test Example 5 Reproducibility and stability test

[0091] In order to study the strength of the adsorption effect of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres on malachite green dye, the same adsorption conditions as malachite green were used to adsorb 5 different pigments (methyl blue, acridinium yellow, methylene blue, carmine and gentian violet). The results are as follows Figure 8 As shown in A, the adsorption capacity of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres for malachite green dye is much higher than that of the other five pigments, indicating that PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres have a certain selectivity for malachite green dye.

[0092] Good reproducibility and stability are important properties that new composite materials must possess. In order to explore the reproducibility of the prepared PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres, Figure 8 As shown in B, malachite green was adsorbed and after 6 extraction-analysis cycles, the elution rate was above 90%, indicating that PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres have good repeatability, reduce the cost of the experiment and meet the requirements of green environmental protection.

[0093] To explore the stability of the composite material, the PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres were dried and sealed at 60°C for 25 days. Every 5 days, 300 mg of PAAM-SA / Fe3O4@MOF-545 hydrogel microspheres were placed in 10 mL of solvent for adsorption and elution. The results showed that ( Figure 8 C. Figure 8 D) With the increase of storage time, the adsorption efficiency and elution rate of the material can remain stable, and the decolorization rate and elution rate are both above 90%, indicating that the material has strong stability.

[0094] Test Example 6 Analysis of Actual Samples

[0095] UPLC-MS / MS was used to detect malachite green solutions with concentrations of 0.3, 0.4, 1, 1.5, 2.5, 10, and 20 μg / ml. The results showed that the malachite green solution had a good linear relationship in the range of 0.3-20 μg / L. The obtained standard curve equation was y=23.957x-2.984 (x is the concentration of the malachite green solution, y is the corresponding peak area), r 2 =0.998. Under this condition, the detection limit and quantification limit of malachite green solution were 0.014 and 0.052 μg / ml respectively. When malachite green standard solution with concentrations of 0.5, 1, and 5 μg / ml was added to the blank matrix, the recovery rate was 94% and the standard deviation was 1.732. It can be determined that this method has a high accuracy for the determination of malachite green in fish meat.

[0096] This material was used for experimental detection and analysis in actual samples to verify the feasibility of the experiment. Yellow croaker was used as the experimental detection object. After immersing it in acetonitrile to precipitate malachite green, Fe3O4hydrogel@MOF-545 was added for adsorption extraction to enrich the malachite green in the sample. HPLC-MS / MS was used for testing. As shown in Figure 3, it can be found that Fe3O4hydrogel@MOF-545 can be used for the detection of low-concentration malachite green in actual samples, which shortens the pretreatment time and simplifies the pretreatment steps. The accuracy of malachite green adsorption detection is significantly improved. It is a new composite material with portability, high efficiency, high controllability and stability.

[0097] Table 3 Test data of actual samples before and after enrichment

[0098]

[0099] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A magnetic metal organic framework hydrogel composite material, characterized in that: The magnetic metal organic framework hydrogel composite material is obtained by compounding magnetic metal organic framework particles and hydrogel; The magnetic metal organic framework particles are particles of MOF-545 coated with Fe3O4; The hydrogel is a cross-linked polymer network formed by polymerization of polyacrylamide and sodium alginate; The magnetic metal organic framework is dispersed in the cross-linked polymeric network.

2. The magnetic metal organic framework hydrogel composite material according to claim 1, characterized in that: The surface of the magnetic metal organic framework hydrogel composite material has a small pore structure formed by grooves and unevenness.

3. The magnetic metal organic framework hydrogel composite material according to claim 1, characterized in that: The particle size of the magnetic metal organic framework hydrogel composite material is 1 to 5 mm.

4. The method for preparing the magnetic metal organic framework hydrogel composite material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Obtaining magnetic metal organic framework particles; S2, mixing solution A containing magnetic metal organic framework particles, polyacrylamide, an initiator, and a cross-linking agent with solution B containing sodium alginate, and then adding tetramethylethylenediamine to obtain a mixed solution; S3, dropping the mixed solution into a calcium chloride solution, stirring, and filtering to obtain the magnetic metal organic framework hydrogel composite material.

5. The preparation method according to claim 4, characterized in that: In step S2, the initiator is selected from sodium persulfate; Preferably, the cross-linking agent is selected from N,N-methylenebisacrylamide.

6. The preparation method according to claim 4, characterized in that: In step S2, the solid-liquid ratio of magnetic metal organic framework particles to polyacrylamide in solution A is 1 mg: 0.07-0.11 mL; Preferably, the solid-liquid ratio of the magnetic metal organic framework particles to the initiator is 1 mg: 2 to 2.5 μL; Preferably, the solid-liquid ratio of the magnetic metal organic framework particles to the cross-linking agent is 1 mg: 8 to 12 μL; Preferably, the percentage concentration of sodium alginate in solution B is 3.8-4.2 wt %; Preferably, the solid-to-liquid ratio of the magnetic metal organic framework particles to solution B is 1 mg: 0.05-0.1 mL; Preferably, the solid-liquid ratio of the magnetic metal organic framework particles to tetramethylethylenediamine is 1 mg: 0.5-1 μL; Preferably, the concentration of the calcium chloride solution is 0.1 to 0.3 mol / L.

7. The preparation method according to claim 4, characterized in that: In step S3, the stirring conditions include: the stirring time is 0.9 to 1.1 hours.

8. The preparation method according to claim 4, characterized in that: In step S1, the preparation process of magnetic metal organic framework particles includes: S1-1: Fe3O4 magnetic nanoparticles are mixed with polyvinyl pyrrolidone to obtain Fe3O4@PVP magnetic particles; S1-2: The Fe3O4@PVP magnetic particles and MOF-545 are mixed and subjected to a solvothermal reaction I to form a Fe3O4@MOF-545 composite, thereby obtaining the magnetic metal organic framework particles; Wherein, the mass ratio of the Fe3O4 magnetic nanoparticles to polyvinyl pyrrolidone is 1:4-6; The temperature of the solvent thermal reaction I is 85-95° C., the reaction time is 5-7 hours, and the solvent I is N,N-dimethylformamide.

9. The preparation method according to claim 8, characterized in that: In step S1, in step S1-1, the specific preparation process of the Fe3O4@PVP magnetic particles includes: mixing ferric chloride, ferrous chloride and a solvent to obtain a mixture, stirring the mixture and ammonia water at a temperature of 55 to 65°C for 10 to 30 minutes, and obtaining Fe3O4 magnetic nanoparticles after magnetic separation; the Fe3O4 magnetic nanoparticles are mixed with polyvinyl pyrrolidone, vortexed at room temperature for 18 to 22 hours, and obtaining Fe3O4@PVP magnetic particles after magnetic separation; Wherein, the mixing ratio of the ferric chloride, the ferrous chloride and the ammonia water is 50-55g:30-35g:190-210mL; Preferably, in step S1-2, the specific preparation process of the Fe3O4@MOF-545 composite includes: The Fe3O4@PVP magnetic particles, tetrakis(4-carboxyphenyl)porphyrin, ZrOCl2·8H2O and benzoic acid are mixed, subjected to solvothermal reaction I, and magnetic separation is performed to obtain a Fe3O4@MOF-545 composite; The mass ratio of the Fe3O4@PVP magnetic particles to the tetrakis(4-carboxyphenyl)porphyrin is 1:1; The mass ratio of the tetrakis(4-carboxyphenyl)porphyrin, the ZrOCl2·8H2O and the benzoic acid is (40-60):(140-160):(2700-2900).

10. Use of the magnetic metal organic framework hydrogel composite material according to any one of claims 1 to 3 or the magnetic metal organic framework hydrogel composite material obtained according to the preparation method according to any one of claims 4 to 9 as an adsorption material in the separation and determination of malachite green from aquatic products.

Citation Information

Cited By

  • Metal organic framework hydrogel composite membrane, preparation method thereof and application of metal organic framework hydrogel composite membrane in treatment of antibiotics in water

    CN121775675A